Reversals of fortune: Shared governance, “democracy,” and reiterated problem-solving - Thurston, T. L. (Frontiers in Political Science, 2022)
What can the deep past tell us about how “good government” is instituted, replicated, and maintained through time? After a comparative look at late prehistoric political formation in Europe, a case study from Sweden is examined. During the Iron Age, systems of participatory governance developed across Europe, perhaps in response to the autocracies of the previous Bronze Age. Heterarchical structures with systems of checks and balances provided voice for ordinary people, as well as leaders, but there were clear “reversals of fortune,” as autocracy and more egalitarian structures were interspersed through time. The so-called “Long Iron Age” is consequently seen as an extended period of tension between different forms of government, different political ideologies, and the dynamic negotiation of socio-political norms, with repercussions that extend into recent times.